Influence of diabetes on the character of changes of resorption and repair processes in the parodontium and mandibular tissues after tooth extraction - Abramov, A. V.; Hanchev, K. S.; Абрамов, Андрій Володимирович; Ганчев, Кирило Сергійович (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of the work is to find out the pathogenetic characteristics of the reparative component of the post-extraction alveolar socket depending on the time after tooth extraction in experimental diabetes. Materials and methods. In total, 120 sexually mature (age 8–10 months) male Wistar rats, divided into 8 groups of 15 animals each, were used for research. Complex immunohistological, radiographic and biochemical studies were used for the purpose of detailed analysis of the features of the course and mechanisms of development of complications after tooth extraction against the background of DM. In order to assess the state of the innate link of local immunity, the specifics of the course of repair processes at different times of the post-extraction period, the levels of cell proliferation (by expression of Ki-67) and the concentration and content of CD68-positive macrophages in the mucous membrane were determined immunohistochemically. In order to determine the state of the bone tissue of the dental and jaw apparatus and the levels of mineralization of the hard tissues of the molars in the animals of the experimental groups, radiovisiographic images of the right half-mandible were analyzed with determination of the radiographic density. Results. Analysis of proliferative-reparative relationships showed almost no macrophages and very low proliferative activity in the intact periodontium, on the other hand, in DM, initial significant diffuse infiltration by CD68-immunopositive cells with high levels of Ki-67 expression was found. Analysis of X-ray images of the half-mandible revealed that induced DM in rats, even without prior surgical intervention, led to the intensification of resorption processes in bone tissue, which was evidenced by a decrease in radiographic density in the root region of the 1st molar and intraalveolar bone membranes of all three lower molars. Мета роботи – визначити патогенетичні характеристики репаративного компонента постекстракційної альвеолярної лунки залежно від терміну після екстракції зуба при експериментальному ЦД. Матеріали і методи. Під час досліджень використали 120 статевозрілих (вік – 8–10 місяців) щурів самців лінії Wistar, яких поділили на 8 груп по 15 тварин у кожній. Для детального аналізу особливостей перебігу та механізмів розвитку ускладнень після екстракції зуба на тлі ЦД виконали комплексні імуногістологічні, радіографічні та біохімічні дослідження. Для оцінювання стану вродженої ланки місцевого імунітету, особливостей перебігу процесів репарації в різні терміни постекстракційного періоду імуногістохімічно визначили рівні клітинної проліферації (за експресією Ki-67), концентрації та вмісту CD68-позитивних макрофагів у слизовій оболонці. Для визначення стану кісткової тканини зубощелепного апарату та рівнів мінералізації твердих тканин молярів у тварин експериментальних груп проаналізували радіовізіографічні знімки правої напівмандибули з визначенням радіологічної щільності. Результати. Аналіз проліферативно-репаративних зв’язків показав, що в інтактному пародонті майже не було макрофагів, а також дуже низьку проліферативну активність. При ЦД виявлена вихідна істотна дифузна інфільтрація CD68-імунопозитивними клітинами з високими рівнями експресії Ki-67. У результаті аналізу рентгенівських знімків напівмандибул виявлено, що індукований ЦД у щурів навіть без попереднього хірургічного втручання призводив до інтенсифікації процесів резорбції в кістковій тканині. Це підтверджено зниженням радіологічної щільності в кореневій ділянці першого моляра й внутрішньоальвеолярних кісткових мембран усіх трьох нижніх молярів.
Вплив цукрового діабету на характер змін процесів резорбції та репарації в тканинах пародонта та нижньої щелепи після видалення зуба
Abramov A. V. - ORCID ID: 0000-0001-8520-2258; Hanchev K. S. - ORCID ID: 0000-0002-5878-7980.
Keywords: diabetes mellitus; reparation; parodontium; mandible; tooth extraction; radiovisiography; bone density; CD68; Ki-67; rats; цукровий діабет; репарація; пародонт; нижня щелепа; видалення зуба; радіовізіографія; щільність кісткової тканини; щури